Rare bird documentation form for Northern Goshawk at Big Creek State Park, 1981 - Zaletel, Hanket al (1981)
Rare bird documentation form for a Northern Goshawk at Big Creek State Park in Polk County, IA on November 21, 1981. Epson - sheet feed